Myxobacterial Response to Methyljasmonate Exposure Indicates Contribution to Plant Recruitment of Micropredators - Adaikpoh, Barbara I.; Akbar, Shukria; Albataineh, Hanan; Misra, Sandeep K.; Sharp, Joshua S.; Stevens, D. Cole (Frontiers in Microbiology, 2020)
Chemical exchanges between plants and microbes within rhizobiomes are critical to the development of community structure. Volatile root exudates such as the phytohormone methyljasmonate (MeJA) contribute to various plant stress responses and have been implicated to play a role in the maintenance of microbial communities. Bacteriovorous myxobacteria are competent predators of plant pathogens and are generally considered beneficial to rhizobiomes. While plant recruitment of myxobacteria to stave off pathogens has been suggested, no involved chemical signaling processes are known. Herein we expose predatory myxobacteria to MeJA and employ untargeted mass spectrometry, motility assays, and RNA sequencing to monitor changes in features associated with predation such as specialized metabolism, swarm expansion, and production of lytic enzymes. From a panel of four myxobacteria, we observe the most robust metabolic response from plant-associated Archangium sp. strain Cb G35 with 10 micromolar MeJA impacting the production of at least 300 metabolites and inducing a ≥4-fold change in transcription for 56 genes. We also observe that MeJA induces A. sp. motility supporting plant recruitment of micropredators. From these data, we conclude predatory myxobacteria respond to the plant phytohormone MeJA, and exudates could contribute to plant recruitment of micropredators within soils.